2016
DOI: 10.1371/journal.pone.0163357
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of Type Three Secretion System and Quorum Sensing Inhibition of Pseudomonas savastanoi by Polyphenols Extracts from Vegetable Residues

Abstract: Protection of plants against bacterial diseases still mainly relies on the use of chemical pesticides, which in Europe correspond essentially to copper-based compounds. However, recently plant diseases control is oriented towards a rational use of molecules and extracts, generally with natural origin, with lower intrinsic toxicity and a reduced negative environmental impact. In this work, polyphenolic extracts from vegetable no food/feed residues of typical Mediterranean crops, as Olea europaea, Cynara scolymu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 57 publications
1
24
1
Order By: Relevance
“…By using an in vitro plant model system, both these tannin extracts were demonstrated to be able to give a statistical reduction of the hyperplastic symptoms produced by the inoculation of Pseudomonas savastanoi p v. nerii strain Psn23 on cuttings from 2-year-old twigs of Nerium oleander, in comparison to those untreated. In addition, a significant decrease of bacterial multiplication was observed on tannin-treated plants, which was comparable to the in planta growth of the ΔhrpA nonpathogenic mutant of Psn23 [39].…”
Section: Tannins Against Plant Pathogenic Bacteriasupporting
confidence: 54%
See 2 more Smart Citations
“…By using an in vitro plant model system, both these tannin extracts were demonstrated to be able to give a statistical reduction of the hyperplastic symptoms produced by the inoculation of Pseudomonas savastanoi p v. nerii strain Psn23 on cuttings from 2-year-old twigs of Nerium oleander, in comparison to those untreated. In addition, a significant decrease of bacterial multiplication was observed on tannin-treated plants, which was comparable to the in planta growth of the ΔhrpA nonpathogenic mutant of Psn23 [39].…”
Section: Tannins Against Plant Pathogenic Bacteriasupporting
confidence: 54%
“…SR belongs to the ubiquitous and highly conserved proteins of the so-called P-type ATPase family, whose members are present in the cellular membrane of any living organism and involved in numerous transport processes. Conversely, copper suppresses almost completely Ca 2+ -ATPase activity at just 0.1 μM concentration Cu 2+ ions [39].…”
Section: Tannins and Their Mechanisms For Plant Disease Controlmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, plants were found to synthesize compounds that interfere with bacterial QS (Venturi and Fuqua, 2013). It has been shown that mixtures of plant-derived compounds, including extracts (Biancalani et al, 2016;Tiwary et al, 2017), macerates (Ferluga et al, 2007;Subramoni et al, 2011;Rekha et al, 2017) and exudates (Teplitski et al, 2000;Gao et al, 2003;Nievas et al, 2017) interfere with bacterial QS mechanisms. Insight is now being gained into the nature of plant-derived QS modulating compounds that include flavonoids, phenolic acids and terpenoids (Silva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpressing mutant Psn23_pT3-matE was also constructed. The recombinant plasmid pT3-matE (Table S1) was produced starting from the vector pLPVM-T3A, which contains the native promoter of hrpA gene for Psn23 [33]. The matE gene, amplified from pK18-matE using the primers pT3_matE_BamHI_For/pT3_matE_KpnI_Rev, was cloned into the KpnI and BamHI restriction sites of pLPVM-T3A and then electroporated into Psn23 cells.…”
Section: Construction Of Psn23 Mutants For Mate Genementioning
confidence: 99%